Problematika Pengangkatan dan Perberhentian Hakim Mahkamah Agung Terhadap Independensi Kekuasaan Kehakiman Mahkamah Agung Dalam Sistem Ketatanegaraan Di Indonesia - Agustian, Tomi; Setiawati, Dinda; Alexander, Ongky (STAI Bumi Silampari, 2023)
Article 24A paragraph 3 provides a provision that candidates for Supreme Court justices are proposed by the Judicial Commission to the House of Representatives for approval and to subsequently be appointed as chief justices by the president and the Supreme Court Law states that the appointment of Supreme Court Judges is carried out by the President on the proposal of the House of Representatives or the dismissal of the Chairman, Vice Chairman, Junior Chairman, and Member Judges of the Supreme Court is dismissed by the President on the proposal of the Supreme Court, so that the President, the House of Representatives (DPR, and the Judicial Commission (KY) have loopholes that can later influence the psychic judges in making decisions if the case is related to the 3 (three) institutions. This study aims to determine the Independence of Judicial Power in Indonesia. This research includes library research, research whose data sources are obtained through good literature sources and laws and regulations and using normative and juridical approaches, the Compiler concludes that the proposal for the appointment and dismissal of Supreme Court judges by the Judicial Commission, the House of Representatives and the President may affect the psychic of a judge in making a decision so that this can eliminate the meaning of Article 24 paragraph 1 of the 1945 Constitution which shows less independence of judicial power in upholding justice in accordance with the ideals of the 1945 Constitution.